O reconhecimento da alteridade como possibilidade de construção de um novo paradigma na cultura ocidental em Joel Birman e Emmanuel Lévinas - Estevam, José Geraldo (Horizonte, 2008)
The Western Culture based on the aegis of the Greek ontology, has historically relegated the other in his alterity to the forgetfulness, in supremacy of the Being who justified the crusades, the colonization, the slavery, the totalitarian regimes like the Fascism and the Nazism, among others. It is in this perspective that this article has as objective to present the perspectives of the teacher Joel Birman and of the philosopher Emmanuel Lévinas on the importance of constructing a new paradigm in the western culture that recognizes the alterity. This paradigm which recognizes the alterity of other is an unpublished opening of myself, who surpasses the egocentric logic of the Being. The approach of Birman consists of reading, from the psychoanalysis, of the causes and consequences of the narcissism culture, that leads society of spectacles in the post-modernity, which while be centering in myself, it does from another object for his selfish satisfactions. The approach of Lévinas is already a philosophical criticism on the primacy of the ontology, which from his origin in ancient Greece, disregarded other in a negation of the alterity in a violent form. The proposal Levinasiana is the one that the ethics precedes the ontology, in other words, the ethics as first philosophy must lead the relation between the men, in recognition of other in his alterity. It is important to find out that it's not intention of this short work to analyze in details the conceptions of Birman neither of Lévinas, but to highlight the similarities between their thought in spite of the differences between their approaches regarding to the question of the alterity in the western culture.